Selective Inhibition by 2-Bromoethanesulfonate of Methanogenesis from Acetate in a Thermophilic Anaerobic Digestor - Zinder, S. H. (1984)
The effects of 2-bromoethanesulfonate, an inhibitor of methanogenesis, on metabolism in sludge from a thermophilic (58°C) anaerobic digestor were studied. It was found from short-term experiments that 1 μmol of 2-bromoethanesulfonate per ml completely inhibited methanogenesis from (14)CH(3)COO(−), whereas 50 μmol/ml was required for complete inhibition of (14)CO(2) reduction. When 1 μmol of 2-bromoethanesulfonate per ml was added to actively metabolizing sludge which was then incubated for 24 h. it caused a 60% reduction in methanogenesis and a corresponding increase in acetate accumulation; at 50 μmol/ml it caused complete inhibition of methanogenesis and accumulation of acetate. H(2), and ethanol.